European Regional Policy and Development in Greece: Do Statistics Justify the Investments? - Iason Koufodontis; Andreas Alexopoulos; Eleni Gaki (European Regional Science Association (ERSA), 2010)
The study presented in the paper attempts to examine if the alleged effectiveness of the developmental funds - one of the main strategic tools of the EU - can be traced in the typical statistics provided by various authorities and organizations. The study focuses in the case of funds used in Greece during a period of years and it tries to provide insight in the issue, based on statistical and empirical data analysis methodologies. Available information regarding European programmes and corresponding funds is charted and linked to relevant official statistical data provided by Greek national authorities and Eurostat. Selected sectoral and regional actions are analyzed based on an optimal match between funding objectives and official statistics. The results, both statistical and empirical, appear to support the argument: assessment of EU regional policy based on statistics does not seem to be a conclusive method of evaluation.
Keywords: 330; EU funds; regional development; developmental statistics; policy effectiveness; territorial cohesion; policy evaluation